Meiotic irregularities in Alstroemeria andina var. Venustula (Alstroemeriaceae) - Sanso, Andrea Mariel (2007)
Alstroemeria andina Phil. var. venustula (Phil.) M. Muñoz (sub nom. A. andina Phil. subsp. venustula (Phil.) Ehr. Bayer) is a perennial, small herb, 5-16 cm tall, that occurs mainly at 2,800-3,700 meters above sea level, in populations of limited distribution from Argentina and Chile. The course of the meiosis was analyzed in a population of this taxon (2n = 2x = 16), and it proved to be highly irregular. It was characterized by presenting bridge and fragment configurations both at anaphases I and II. The highest number of bridges at anaphase I found in one cell was two, suggesting heterozygosity for as many as two paracentric inversions. Typical chiasmata were almost not detectable, even though they actually existed. The chiasma-like structures observed may be regarded as concealed chiasmata as it has been described in cryptochiasmate meiosis. A high frequency of tetrads with micronuclei was observed, implying significant levels of unbalanced gametes. Pollen stainability ranged between 28 and 30%. In Alstroemeria species the meiotic behaviour is highly regular, and the presence of rearrangements is very uncommon. The whole situation led us to suggest that some environmental factors have drastically affected the chromosome structure and the control of the meiotic process. The present study constitutes the first report of remarkable meiotic irregularities found in a wild population of this genus.